Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual, Perilaku Belajar dan Latar Belakang Pendidikan Menengah Terhadap Tingkat Pemahaman Akuntansi(Studi Empiris pada Mahasiswa Akuntansi Universitas Muhammadiyah Surakarta Dan Universitas Sebelas Maret) - Wahyuni, wahyuni; , Fauzan, SE, Ak, M.Si (2016)
Understanding of accounting is a person's ability to know and understand about accounting. Through the level of nderstanding of accounting can be known how adequate ccounting knowledge already possessed an accountant in order to carry out the role of the accounting profession in the world of economics and business. The purpose of this research was to examine the effect of intellectual ntelligence, emotional intelligence, spiritual ntelligence, learning behavior and background of secondary education to the understanding of accounting in accounting student Faculty of Economy and Businness at Muhammadiyah University of Surakarta and Sebelas Maret University This research uses primary data is to provide the questions in the form of a questionnaire distributed to respondents. Methods of data analysis was done with descriptive statistical testing, quality testing data and assumptions of classical before hypothesis test. Testing the hypotheses used in this research is the analysis of multiple linear regression with coefficient test, f test and t test. The results of this research showed that intellectual intelligence, emotional intelligence and spiritual intelligence affect the level of understanding of accounting. While learning behavior and background of secondary education does not affect the level of understanding of accounting. Keywords:intellectual intelligence, Emotional Intelligence, spiritual intellegence, Learning Behavior,Background of Secondary Education, Degree of AccountingUnderstanding